Implementasi Manajemen Strategi dalam Meningkatkan Mutu Pendidikan di Pondok Pesantren - Muhammad Taufik; Siti Patimah; A.Latief Arung Arafah; Andi Warisno (Departement of Mathematics Education, 2024)
The quality of education will not be successful without the right strategy to improve every aspect that influences it, such as teacher professionalism, graduate competency standards, learning effectiveness, and programs that support quality achievement. One step to improve quality is through the implementation of strategic management which can help determine appropriate strategies to improve the quality of education. This research aims to analyze strategic management, and identify the results of implementing strategic management in improving the quality of education at the Darul Qur'an Wadda'wah Argapura Islamic Boarding School, Jayapura City, Papua. The research method used is a qualitative descriptive method, with data collection techniques through interviews, observation and documentation studies. The research results show that strategic management in improving the quality of education at the Darul Qur'an Wadda'wah Argapura Islamic Boarding School, Jayapura City, Papua goes through four stages, namely environmental analysis, formulation, implementation and evaluation. Environmental analysis includes an evaluation of internal strengths and weaknesses as well as external opportunities and threats. Strategic management formulation includes the development of school vision, mission, goals and strategies. Implementation of strategic management involves implementing the Eight National Education Standards as well as managing the curriculum, student activities and facilities well. Strategic management evaluation is carried out through several types of evaluation, including program evaluation by the school principal or person in charge, academic evaluation, and school evaluation meetings. Supporting factors in improving the quality of education include adequate facilities and good relationships with parents and boarding schools. However, factors such as inadequate teacher qualifications, disruption in the learning process, and competition with other Islamic boarding schools are obstacles to achieving quality education at the Islamic boarding school.